Analysis on the Effectiveness of Implementing Journal Vocabulary Strategy in Reading Comprehension Texts - Pipit Syahara, Wariyati (ALACRITY : Journal of Education, 2023)
Vocabulary is the main thing that needs to be known in English, without vocabulary no one can speak English. Many students at school do not know vocabulary in English. Therefore an effective strategy is needed for students to be able to find vocabulary easily, especially when reading in English. Understanding the vocabulary is highly needed to makes students easy in learning. This study aims to examine the use of a learning strategy, namely journal vocabulary in reading comprehension texts. The research method used is library research (literature study) from 5 journals in Indonesia in the period 2013-2023. The results of the study show that the use of journals vocabulary is very effective for students. Journals vocabulary can help them to enrich their vocabulary knowledge, because it is easier for them to memorize vocabulary. In addition, the use of journals vocabulary also increases their independence in learning English vocabulary and journal vocabulary can facilitate them to track their progress in vocabulary knowledge and make it easier for them to understand reading texts. Thus, the use of journals vocabulary is really necessary for students so that they can learn English more pleasantly in the classroom by using this strategy. These results are expected to contribute ideas for skills in the field of English, especially the learning strategy because it has unlimited benefits in the field of education to be developed.